2005
DOI: 10.1021/ci0496189
|View full text |Cite
|
Sign up to set email alerts
|

A General Treatment of Solubility. 3. Principal Component Analysis (PCA) of the Solubilities of Diverse Solutes in Diverse Solvents

Abstract: A phenomenological study of solubility has been conducted using a combination of quantitative structureproperty relationship (QSPR) and principal component analysis (PCA). A solubility database of 4540 experimental data points was used that utilized available experimental data into a matrix of 154 solvents times 397 solutes. Methodology in which QSPR and PCA are combined was developed to predict the missing values and to fill the data matrix. PCA on the resulting filled matrix, where solutes are observations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 25 publications
1
76
0
Order By: Relevance
“…It was found that all three force-fields showed systematic deviations from experimental data [18,19], with OPLS-UA and GROMOS overestimating the magnitude of solvation (by 15% and 13%, respectively), and TraPPE slightly underestimating it (by 6%) [17]. This performance was rationalized on the basis of the parameterization strategy and target experimental properties used by each model.…”
Section: -Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…It was found that all three force-fields showed systematic deviations from experimental data [18,19], with OPLS-UA and GROMOS overestimating the magnitude of solvation (by 15% and 13%, respectively), and TraPPE slightly underestimating it (by 6%) [17]. This performance was rationalized on the basis of the parameterization strategy and target experimental properties used by each model.…”
Section: -Introductionmentioning
confidence: 90%
“…However, it appears that within this range of values, the influence of the solute-solvent attraction dominates and the excluded volume effect is rather minor. [18,19], while the thin dashed lines represent upper and lower bounds based on the estimated uncertainty in experimental measurements [40].…”
Section: -Cyclic Alkanesmentioning
confidence: 99%
See 3 more Smart Citations